(untitled) (Raparin Journal of Humanities (RJH), 2024)
The study examines how Japanese haiku poetry, which has been popular in American poetry since the turn of the 20th century, was revisited by Fady Joudah. The paper argues that current Arab-American poetry’s avant-gardism is best shown by Joudah’s appropriation of this poetic form in his poetry collection, Textu. Joudah’s new poetic genre tackles topics pertaining to the Arab-American identity in the digital era by utilizing avant-garde approaches. The suggestiveness of Haiku, which emphasizes the visual picture, word accuracy, and clear diction, is brilliantly appropriated by Joudah. The paper significantly demonstrates how a smartphone can condense pages of invocations and disclosures. It contends that Jouda’s text message-like poems, which are each restricted to 160 characters, may most effectively capture the hurried spirit of the twenty-first century represented by its growing use of cell phones’ texting and twittering.